Beyond TGFβ1 - novel treatment strategies targeting lung fibrosis. (December 2021) - Sim, Claudia; Lamanna, Emma; Cirnigliaro, Frank; Lam, Maggie
Abstract: Fibrosis is a key feature of chronic lung diseases and occurs as a consequence of aberrant wound healing. TGFβ1 plays a major role in promoting fibrosis and is the primary target of current treatments that slow, but do not halt or reverse the progression of disease. Accumulating evidence suggests that additional mechanisms, including excessive airway contraction, inflammation and infections including COVID-19, can contribute to fibrosis. This review summarises experimental and clinical studies assessing the potential beneficial effects of novel drugs that possess a unique suite of complementary actions to oppose contraction, inflammation and remodelling, along with evidence that they also limit fibrosis. Translation of these promising findings is critical for the repurposing and development of improved therapeutics for fibrotic lung diseases.